Relationship Between by Catch Ratio of Sardine-Anchovy Targeted Purse Seine and Some Environmental Factors Based on a General Addictive Model in the Aegean Sea - Zafer Tosunoğlu; Tevfik Ceyhan (Aquatic Sciences and Engineering, 2022)
By catch is a serious conservation challenge for the fisheries whose viability is increasingly under threat. To approach maximum by catch reduction with minimum loss of targeted catch, fisheries need to have information on the environmental and anthropogenic factors in multi species seas like the Mediterranean. In this study, we used generalized additive models (GAM) to by the catch ratio of purse seine fishery to determine the effects of environmental variables. The data were col-lected during each fishing trip in the 2018-2019 fishing season that covers the time period between September 1st and April 15th. There were 26 species (66.216 mt in total) recorded as by catch and the rates of by catch species in the total by catch amount varied between 0.001% and 23.1%. In terms of habitat of by catch species, the total ratios of benthopelagic, demersal and pelagic spe-cies were 52% , 28% and 20%, respectively. Significant interactions observed indicate that the fluc-tuations in by catch ratios differed by depth and sea surface temperature, whereas the quarters of year and the moon phases were not found to affect by catch ratios significantly.